59.0k views
4 votes
Solve the equation. - 4(r + 6) = -54

2 Answers

2 votes

- 4(r + 6) = -54​

expand

-4r - 24 = -54

add 24 to both sides

-4r = -54 + 24

-4r = -30

Divide both sides by -4

r = -30/-4

r = 7.5

User Graham
by
5.6k points
4 votes

Answer:


\boxed{\sf{r=(15)/(2)=7.5 }}

Explanation:

Use the distributive property.

a(b+c)=ab+ac

-4(r+6)=-54

Isolate the term of r from one side of the equation.

You have to divide by -4 from both sides.


\sf{(-4\left(r+6\right))/(-4)=(-54)/(-4)}

Solve.

-54/-4=27/2

r+6=27/2

Subtract by 6 from both sides.

r+6-6=27/2-6

Solve.


\sf{-(6* \:2)/(2)+(27)/(2)}}

-6*2+27/2

Remember to solve this problem, first thing you do is solve with order of operations.

PEMDAS stands for:

  • Parentheses
  • Exponents
  • Multiply
  • Divide
  • Add
  • Subtract

Do multiply first.

-6*2=-12

-12+27

Then add or subtract the numbers from left to right.

-12+27=15

r=15/2

Divide is another option.

15/2=7.5


\rightarrow \boxed{\sf{r=(15)/(2)=7.5}}

Therefore, the correct answer is r=15/2=7.5.

I hope this helps, let me know if you have any questions.

User Ryan Stanley
by
5.3k points